Drugs importation and the bifurcation of risk. Capitalization, cut outs and organized crime - Dorn, Nicholas (The British journal of criminology, 1998)
Qualitative research was conducted with 15 persons convicted of serious offences in connection with drugs importation into the UK, and with 10 informants of Her Majesty's Customs and Excise, with appropriate safeguards.1 Objectives included an assessment of smugglers' planners' and organizers' perceptions about risk' and how they attempted to reduce risk. Two conceptually distinct forms of risk were identified. Strategic risk is the risk to the planner/organizer number 1' man or woman. Tactical risk is the risk to the drugs and to persons other than the planner/organizer. This paper focuses on strategic risk, which is described as differing markedly between a the well capitalized, risk-adverse number 1, who is well cut out' from danger, and b the more risk-tolerant, hands on' number 1, who is more directly associated with the drugs and other vulnerable aspects of smuggling operations. The authors give reasons for focusing future work on interactions between the first category of trafficker and control strategies